Implementation of Demand and Supply Functions Related to The Application of Mathematical Science to MSME Products in Pelawi Utara Village, Babalan, Langkat Regency - Nina Fadilah; Ikhah Malikhah; Wachyuni, Minarti Sri; Rahmadani, Nanda Puspa; Ramandha Ramandha (International Journal of Science and Mathematics Education, 2024)
This study analyzes related to the application of mathematical concepts to the demand and supply function of MSME products in North Pelawi Village, Babalan District, Langkat Regency. The results show that there is an elasticity associated with mathematical concepts for the demand function and the supply function. Usually, because MSME products are hampered by supply chain disruptions and production. However, through recovery strategies and interventions to apply mathematical concepts in the demand and supply functions, a balance curve between the demand and supply functions is formed. Awareness to apply mathematical concepts for business actors has an important role in controlling the rate of supply of goods so that the number of goods demand can be fulfilled according to the number of desires and the prices offered can be adjusted to the prices requested by consumers. This research highlights the importance of awareness and understanding the role of business actors who are aware of the application of mathematical concepts so that regulating demand and supply can run systematically and not damage the market price offered to consumers.